Immigrant workers in industrial France : the making of a new laboring class - Cross, Gary S. (Book collections on Project MUSE., 1983)
In Immigrant Workers in Industrialized France, Gary Cross blazed the trail of immigrant studies with this finely wrought study at the crossroads of labor studies and immigration history. Cross inaugurated in-depth research into the ways in which France welcomed immigrants from the 1880s onward. n an era where many receiving states seek to enforce the "faucet" function Cross so well describes -- opening borders when needed, closing them when perceived not to be -- it is important to read and reread Cross's work.